Chronic Hepatitis Virus B & Chronic Hepatitis Virus C And Clinical Cultures To Study Innate Immune Responses (Journal of Pharmaceutical Negative Results, 2023)
Hepatitis virus causes inflammation of the liver, which inhibits basic liver functions. Different strains of hepatitis viruses are transmitted, infected, and treated in various methods depending on the severity and symptoms of the disease. The World Health Organization estimates around 1.5 million new Hepatitis B infections each year, with around 296 million people living with the infection as of 2019. In order to achieve optimal treatment and understanding of hepatic viruses various 2D and 3D liver cultures have been developed, in which the innate immune response of the liver can be observed through a series of scans and clinical tests. This review elucidates the advantages and disadvantages of various clinical cultures on hepatic viruses (In-Vitro & In-Vivo), and provides prevailing information on Hepatitis B and C Virus infections in humans.